INTERNATIONAL ORGANIZATIONS, THE PRINCIPLE OF SOVEREIGNTY AND THE MANAGEMENT OF INTERNAL POLITICAL CRISES: THE CASE OF THE FRANCOPHONIE AND THE AFRICAN UNION - (:unkn) unknown (My University, 2018)
The management of internal political crises has become the most visible and controversial activity of international organizations today. It is because of this ambivalence that this thesis takes the pretext of the management of political crises by the Francophonie and the African Union to examine the articulation between the political multilateralism and the principle of sovereignty of the States in situation of internal political crisis in Africa. The principal question is to know what remains from the principle of sovereignty in view of the recurrence of the multilateral interventions of these two organizations in issues of strict States sovereignty. The answer is given through a deep analysis of the political, legal and philosophical trajectories of the interaction between State sovereignty and multilateral interferences in the history of Westphalian bill international relations. Moreover, this thesis makes a theoretical retrospective on the question of interferences in general, before dwelling in a specific and empirical way on the interventionist trajectories of the Francophonie and the African Union in Ivory Coast, Madagascar and Central African Republic. The analysis leads to the conclusion that the multilateral management of internal political crises is characterized by its operational complexity: on the one hand, it enables the intervening international organizations to practice a kind of "ransom" for the political freedom of their member States, and on the other hand, it is an opportunity to “instrumentalize” the international organizations that engage in it.
Keywords: African Research